2007
DOI: 10.1021/ic070098j
|View full text |Cite
|
Sign up to set email alerts
|

The First Ruthenium-Based Paullones:  Syntheses, X-ray Diffraction Structures, and Spectroscopic and Antiproliferative Properties in Vitro

Abstract: Two novel paullone derivatives, namely, 6-(alpha-picolylamino)-7,12-dihydroindolo[3,2-d][1]benzazepine (L1) and 9-bromo-6-(alpha-picolylamino)-7,12-dihydroindolo[3,2-d][1]benzazepine (L2), have been prepared. The reaction of cis-[RuCl2(DMSO)4] (DMSO=dimethyl sulfoxide) with L1 and L2 in a 1:1 molar ratio in dry ethanol at 50 degrees C afforded the complexes trans-[RuIICl2(DMSO)2L1] (1a) and trans-[RuIICl2(DMSO)2L2] (1b) in 26 and 30% yield, respectively. The reaction carried out from the same starting compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 58 publications
2
48
1
1
Order By: Relevance
“…The result of the X-ray diffraction study of 4 is shown in Figure 2 exocyclic double bond at the amidrazone moiety, which is in accord with 1 H and 13 C NMR data for 4. Unlike, related amidine 1, derived from 2-picolylamine, adopts a configuration with an endocyclic double bond within the azepine ring [5].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The result of the X-ray diffraction study of 4 is shown in Figure 2 exocyclic double bond at the amidrazone moiety, which is in accord with 1 H and 13 C NMR data for 4. Unlike, related amidine 1, derived from 2-picolylamine, adopts a configuration with an endocyclic double bond within the azepine ring [5].…”
Section: Resultsmentioning
confidence: 98%
“…Since lactams could be converted into amidines and hydrazones providing a binding site for metals, the synthesis of ruthenium complexes with 9-bromo-6-(α-picolylamino)-7,12-dihydroindolo [3,2-d][1]benzazepine (1, Fig. 1) [5,6] and a gallium complex with two N-(9-bromo-7,12-dihydroindolo [3,2-d][1]benzazepin-6(5H)-ylidene-N'-(2-hydroxybenzylidene)azine ligands (3, see Scheme 1) has been performed [7].…”
Section: Indroductionmentioning
confidence: 99%
“…Their properties can be altered by the choice of the ligand, which means that complexes potentially have multiple applications [13e16] and the ability to mimic iron binding to biomolecules [11,17]. Many biological properties have been attributed to ruthenium complexes including antioxidant activity [18] and cytotoxicity [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The search of new metal based pharmaceutical compounds has acquired new impetus during the last few years with the aim to find species that have high activity, low toxicity and with the goal to circumvent the drug resistance [1][2][3][4][5][6][7]. Cancers, inflammations, and diseases of the immune system are often related each other and attract much research efforts.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported by others that treatments with non-steroidal-anti-inflammatory drugs (NSAIDs) protect against lung cancers and breast cancer [8]. The interest on metal complexes with drugs as ligands has much increased because of the improved activities of the complexes when compared to the free ligands and because multi-therapies can stem from the same coordination molecule [6,7,9,10]. Different active functions can be combined in the same molecule through coordination chemistry.…”
Section: Introductionmentioning
confidence: 99%